2000
DOI: 10.1034/j.1399-3046.2000.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning in children on dialysis and post‐transplantation

Abstract: We studied 124 children, 62 patient-subjects who had end-stage renal disease (ESRD) and 62 sibling-controls who closely matched the patient-subjects in terms of their ethnicity and their socioeconomic status, to discern whether children with ESRD would perform less well than their siblings on standardized achievement and intelligence quotient (IQ) tests, and to determine whether ethnicity would influence such results. The subjects were recruited from nine pediatric transplant and dialysis centers across the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 14 publications
8
111
2
3
Order By: Relevance
“…Consistent with earlier investigations of children with severe CKD or mixed severity sample (15)(16)(17)(18), findings from this study revealed that, in general, children with mild-to-moderate kidney disease fall within age-appropriate expectations for IQ, academic achievement, and attention/executive functioning. When individual patients were examined, however, there was a large percentage of children who evidenced risk for dysfunction.…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with earlier investigations of children with severe CKD or mixed severity sample (15)(16)(17)(18), findings from this study revealed that, in general, children with mild-to-moderate kidney disease fall within age-appropriate expectations for IQ, academic achievement, and attention/executive functioning. When individual patients were examined, however, there was a large percentage of children who evidenced risk for dysfunction.…”
Section: Discussionsupporting
confidence: 79%
“…A recent study found cognitive impairment in 49 children after kidney transplantation with a reported Total IQ of M ¼ 83.9, SD ¼ 20.0 (37). Older studies mainly showed deficits regarding nonverbal abilities (38,39). IQs of children after heart transplantation are relative consistently reported to be 10-15 IQ points below nonclinical comparison groups (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…There are also data suggesting that children with more advanced stage CKD, increased duration of disease, and younger age of disease onset are associated with an increased risk of neurocognitive deficit and poor academic outcomes (15,28). By comparison, studies of children with epilepsy also show deficits in intellectual functioning: fullscale IQ mean =85.0 (SD=20.7; n=69), verbal IQ mean =86.9 (SD=22.6; n=69), and performance IQ mean =84.5 (SD=19.4; n=69) (30).…”
Section: Discussionmentioning
confidence: 99%